PENGATURAN MENGENAI PRAMUWISATA ASING DI BALI - Darma Yasa, Putu Gede; Gatrawan, I Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014, 2014)
The tour guide is an attempt to provide and coordinate energy tour guides to meet the needs of tourists and the needs of tour operator. The increasing visits of foreign tourists to Bali is not coupled an increasing number of foreign-controlled language tour guide. This condition is exploited foreign tourists to be a tour guide for other travelers. The problem has occur is whether foreign nationals can become a tour guide in Bali. This paper used empirical legal research methods. The conclusions obtained are regulation local of Bali province No. 8 of 2005 about the tour guide and local regulation of Bali No. 1 in 2010 about Travel Services Business was the basis regulation which is prohibiting foreign nationals into a tour guide in Bali. Second, the legal sanctions that may be applied, namely in the form of criminal confinement of not longer than 6 (six) months or a maximum fine of Rp. 10,000,000 (ten million rupiah).
Keywords: Guides, Bali, local regulations